Power, ethics, and person-centred care: using ethnography to examine the everyday practices of unregistered dementia care staff - Scales, Kezia; Bailey, Simon; Schneider, Justine M. (Blackwell Publishing, 2017)
The social positioning and treatment of persons with dementia reflects dominant biomedical discourses of progressive and inevitable loss of insight, capacity, and personality. Proponents of person-centred care, by contrast, suggest that such loss can be mitigated within environments that preserve rather than undermine personhood. In institutional settings, person-centred approaches place particular emphasis on ‘empowering’ unregistered care staff to translate this idea into practice. These staff provide the majority of hands-on care, but with limited training, recognition, or remuneration. Working within a Foucauldian understanding of power and the ethical constitution of subjects, this paper examines the complex ways that dementia care staff engage with their own ‘dis/empowerment’ in everyday practice. The findings, which are drawn from ethnographic studies of three National Health Service (NHS) wards and one private care home in England, are presented as a narrative exploration of carers’ general experience of powerlessness, their inversion of this marginalised subject positioning, and the related possibilities for action. By examining the daily dilemmas that care staff navigate, this paper contributes to our understanding of the complex risks and responsibilities entailed in direct care work, with implications for the provision of ethical and person-centred dementia care.